Método para implantação de um sistema de gestão da qualidade baseado na norma ISO 9001:2000. - Leite, Daniela Cristina Medeiros (Universidade Federal de São Carlos, 2005)
The family of ISO 9000 standards is being constantly adopted by the companies, manufacturing and services, as a base to implement a quality management system. With the 2000 review, the ISO 9000 has progressed from a quality assurance system to a quality management system, incorporating the eight total quality principles. For this reason, in order to companies achieve success in the ISO 9001:2000 implementation, it is necessary that these principles become part of their culture, because there is a cultural gap between the quality assurance and quality management concepts. In this context, the objective of this study is propose a method of implementing a quality management system (QMS), based on the ISO 9001:2000 standard, considering, beyond the requirements demanded by the standard, aspects related to company culture, human resources qualification and use of continuous improvement methods and tools. The development of this study happened through an action research, using the method SSA (Soft System Analysis), in a leather industry, which was at an intermediate phase of ISO 9001:2000 standard implementation. The finds achieved in the research showed that the method proposed was adequate to the initial objective, because it suggests actions that can minimize or eliminate the gaps existent in a quality management system, and helped the company to achieve a considerable improvement in its QSM. Besides, it was possible to conclude that the ISO 9001:2000 standard should not be implemented only through written procedures and training routines, but aspects like company culture and human resources should also be considered.
Keywords: Gestão da qualidade; ISO 9001; ISO 9000; Certificação da qualidade; Quality management system; Quality; ISO 9000; ISO 9001:2000; ENGENHARIAS::ENGENHARIA DE PRODUCAO